ANALISIS KINERJA KEUANGAN DAERAH KABUPATEN SIGI - Yuli, Norma (Katalogis, 2017)
The objectives of this study are: 1) to find out analyze the regional financial performance based on growth rate of Sigi Regency; 2) to find out and analyze regional financial performance based on effectiveness and Efficiency ratio of regional revenue of Sigi Regency; 3) to find out and analyze regional financial performance based on financial independency ratio of Sigi Regency; 4) to find and analyze the level of fiscal independency and regional autonomy level of Sigi Regency. The result shows that the regional growth rate ratio ini 2010 was Rp. 473.772.844.736 and in 2014 reached Rp. 761.741.007.226. the growth of rate regional expenditure ratio in 2010 was Rp. 463.412.362.554 and in 2014 was Rp. 747.623.458.900. effectiveness ratio in five years has show a high effectiveness and Efficiency ratio in three years highly Efficiency. Activity ratio was more fluctuated 73% and 77% in 2010 and 2014 respectively. Indendency ratio has shown instructive level or less independent with independency level of 2-3%.